Pathophysiology and management of reperfusion injury and hyperperfusion syndrome after carotid endarterectomy and carotid artery stenting. (December 2016) - Farooq, Muhammad; Goshgarian, Christopher; Min, Jiangyong; Gorelick, Philip
Abstract Cerebral hyperperfusion is a relatively rare syndrome with significant and potentially preventable clinical consequences. The pathophysiology of cerebral hyperperfusion syndrome (CHS) may involve dysregulation of the cerebral vascular system and hypertension, in the setting of increase in cerebral blood flow. The early recognition of CHS is important to prevent complications such as intracerebral hemorrhage. This review will focus on CHS following carotid endarterectomy and carotid artery stenting. We will discuss the typical clinical features of CHS, risk factors, pathophysiology, diagnostic modalities for detection, identification of patients at risk, and prevention and treatment. Although currently there are no specific guidelines for the management of CHS, identification of patients at risk for CHS and aggressive treatment of hypertension are recommended.